Analisis Gaya Bahasa Dan Makna Dalam Lirik Lagu “RAYUAN PEREMPUAN GILA” Karya Nadin Amizah - Muthia Azahra (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2025)
This research contains a discussion of the use of language styles in the lyrics of the song by Nadin Amizah with the title "Rayuan Perempuan gila" and the meaning in the song lyrics. The aim of this research is to analyze the use of language styles and the meaning of language styles in the song "Rayuan perempuan gila". This research uses descriptive research and a qualitative approach which is guided by the theory of Gorys Keraf (2010). The song "Rayuan Perempuan Gila" was chosen as research material because the song's lyrics were written using a language style that was quite interesting and quite foreign to the ears of the wider community. However, this song by Nadin Amizah was well received by the wider community. The research was carried out using the literature study method, so that from this research it is hoped that results will be found in the form of discovering types of use of language style and meaning in the song entitled Mad Woman by Nadin Amizah. The results of this research are the discovery of language styles found in Nadin amizah is the eufimisme style of language, the simile style of language and the litotes style of language